Prevention and resolution of foreign exchange crises in East Asia - Chalongphob Sussangkarn (Asian Development Bank Institute (ADBI), 2012)
This paper discusses mechanisms to prevent and resolve foreign exchange crises in East Asia. Policies and mechanisms at the country level as well as regional and global levels are discussed. Policies at the level of a particular country to prevent foreign exchange crises include the management of short-term foreign currency liabilities, the adequacy of reserves, and managing episodes of rapid short-term capital inflows. The author discusses the development of regional mechanisms for crisis prevention and resolution in conjunction with the global mechanisms, including the Chiang Mai Initiative (CMI) and the Chiang Mai Initiative Multilateralization (CMIM). The author then suggests how the CMIM can evolve into an integrated crisis prevention and resolution mechanism for East Asia.
Keywords: E02; E44; E58; E63; F33; F36; F55; 330; foreign exchange crises; east asia; chiang mai initiative; Währungskrise; Währungsrisiko; Wechselkurspolitik; Kapitalverkehrskontrolle; Ostasien